Targeting Keap1/Nrf2/ARE signaling pathway in multiple sclerosis - Michaličková, Danica; Hrnčíř, Tomáš; Canová, Nikolina Kutinová; Slanař, Ondřej (European journal of pharmacology, 2020)
Multiple sclerosis (MS) is a neurologic autoimmune disorder featured by chronic inflammation of the central nervous system, demyelination and axonal damage. Recently, the term "oxinflammation" has been proposed to depict the vicious circle of chronic inflammation and oxidative stress (OS). OS promotes demyelination and neurodegeneration directly, by oxidation of lipids, proteins, and DNA but also indirectly, by inducing a dysregulation of the immunity and favoring the state of pro-inflammatory response. Many of the actors of this delicately tuned network are controlled by Keap1/Nrf2/ARE signaling pathway, a principal regulator of antioxidant and phase II detoxification genes. This pathway also has a pivotal role in inflammation, and therefore possesses a great potential in the treatment of MS. The aim of this review is to provide the newest insights in the preclinical and clinical evidence of Nrf2 induction in the regeneration of the antioxidant response and attenuation of inflammation in MS. Preclinical studies have indicated that activators of this pathway, such as epigallocatechin gallate (EGCG), curcumin, melatonin, resveratrol, and sulforaphane might be a promising therapeutic option in amelioration of MS symptoms, nevertheless, the efficacy and safety of these compounds have to be confirmed in future clinical trials.
Keywords: signální transdukce; Vesicular Transport Proteins; Resveratrol; Antioxidants; NF-E2-Related Factor 2; roztroušená skleróza; Nrf2 inducers; lidé; Signal Transduction; Curcumin; Multiple Sclerosis; Flavonoids; zvířata; Humans; Kelch-Like ECH-Associated Protein 1; Melatonin; Oxidative stress; faktor 2 související s NF-E2; KEAP-1; Neuroinflammation; EGCG; vezikulární transportní proteiny; Animals